Obstacles and Challenge of Law Enforcement in the Face of Mayantara Crime in Indonesia - Maulana Arif Fadli; Muhammad Hatta; Isvani Isvani; Angga Dhipinto; Devia Anjelia; Rafita Sari (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The rapid development of information and communication technology (ICT) has increased the risk of cybercrime in Indonesia. Law enforcement against this crime faces various obstacles and challenges, both in terms of regulations, the capacity of law enforcement officials, and public awareness. This study aims to analyze the obstacles and challenges in law enforcement against violent crime in Indonesia and provide recommendations to improve its effectiveness. Through a qualitative approach with a case study method, this study uses primary data from interviews with law enforcement officials, academics, and cybersecurity practitioners, as well as secondary data from laws and regulations and related reports. The results of the study show that existing regulations, such as the Electronic Information and Transaction Law (ITE Law), still have weaknesses in accommodating the development of cybercrime. In addition, limited human and technological resources in law enforcement institutions, as well as low public awareness of cybersecurity, also hinder the effectiveness of law enforcement. To address these challenges, the study recommends more adaptive regulatory revisions, capacity building of law enforcement officials through more advanced training and technology, and public education campaigns to increase public awareness of cybersecurity. In addition, international cooperation needs to be strengthened to deal with transboundary crimes.